POTENSI AIRTANAH PADA AKUIFER REKAHAN BATUAN BEKU BERDASARKAN DATA GEOLISTRIK DAN UJI PEMOMPAAN DI ULUBELU GEOTHERMAL POWER PLANT PROJECT, PROVINSI LAMPUNG - Novandi Kusuma Prasetya Wangsadiria (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2013)
Water was needed to be supplied to the cooling tower of Ulubelu Geothermal Power Plant Project area. The use of surface water was not recommended due to the impact that would occured to agricultural and plantational sector around the area. Hence, the study of groundwater resources on the aquifer of fractured igneous rock by geoelectric and pumping test data was performed.The objectives of the study consists of determining the typical, depth and characteristic of aquifer, establish the value of well efficiency, coefficient of transmissivity (T), coefficient of permeability (K) and coefficient of storage (S), establish the class, characteristic and type of groundwater chemistry and its relation to the environment, and define the qualitative and quantitative of groundwater potential on the field study. The methods were using resistivity and pumping test analysis, and supported by groundwater chemistry analysis, borehole log, petrography and outcrops observation. Geoelectric method was using pole-pole configuration as much as 8 lines. Pumping test consists of step drawdown test, constant rate test and recovery test.The correlations of 2D resistivity cross-section and inversion model were using Rockwork and obtained 3D visualization of zone of fractured aquifer potential. The depth of aquifer was ranging 75-150 m with water table about 50-65 m. Pumping test has carried out on well Mella-01, Mella-02 and Mella-03. The results obtained good well efficiency that is more than 90%. Coefficient of transmissivity and coefficient of storage were calculated using Theis recovery method and obtained T 3,441-5,205 m2/day and S 0,022-0,054. The value of S showed that the type of aquifer is unconfined. Coefficient of permeability 0,681-0,713 m/day and supported by petrography analysis indicates the characteristic of fractured igneous rocks. Groundwater quantity was obtained 192 m3/day and the quality indicated by the type of groundwater chemistry that rank of carbonate and semi-carbonate type. Considering from the neutral pH, total dissolved solids, EC and Chloride content, groundwater was categorized fresh water.